A photo-activated process cascaded electrocatalysis for the highly efficient CO2 reduction over a core–shell ZIF-8@Co/C. Issue 32 (4th August 2020) - Gu, Jian-Xia; Zhao, Xue; Sun, Yue; Zhou, Jie; Sun, Chun-Yi; Wang, Xin-Long; Kang, Zhen-Hui; Su, Zhong-Min
Abstract : A photo-activated process is cascaded to an electrocatalytic pathway for reducing CO2 to prepare syngas over core–shell ZIF-8@Co/C, exhibiting excellent electrochemical performance and achieving high joule-to-joule conversion efficiency of 5.38%. Abstract : Light irradiation can affect electronic properties of catalysts and the introduction of appropriate light into electrocatalysts may have a significant impact on the electrocatalytic process; however, this has not been fully studied. Herein, we propose a photo-activated process cascaded electrocatalysis for CO2 reduction to produce syngas over a core–shell ZIF-8@Co/C catalyst. Under light irradiation, the onset potential and overpotential of ZIF-8@Co/C positively shift by 40 and 200 mV, and the syngas production is enhanced 5.2-fold at a bias potential of −0.9 V vs. RHE. It is noteworthy that the electric energy efficiency is enhanced by 30%. Deducting syngas generated by electricity, the solar-to-syngas conversion efficiency (joule to joule) is as high as 5.38%, which outperforms reported photoelectrochemical systems. These devices also relatively maintain high efficiency in neutral pH aqueous solution. Dedicated experiments and in situ transient photovoltage studies demonstrate that the cascaded photo-activation of CO2 and H + in electrocatalysis accounts for the outstanding catalytic performance.